Effect of Capital Intensity, Advertising Expense and Inventory Intensity on Tax Aggressiveness - Fitri Rodearni Panggabean; Anggun Anggraini (Formosa Journal of Sustainable Research, 2023)
The purpose of this study is to determine the effect of Inventory Intensity, Marketing Expense, and Capital Intensity on the Tax Aggressiveness of Industrial Manufacturing Sector Companies Listed on the Indonesia Stock Exchange (IDX). Companies in the manufacturing industry sector are listed on the Indonesia Stock Exchange from 2017 to 2017 in 2021 will be the research population. In this study, 38 samples from 8 companies were sampled using purposive sampling method and observed for 5 years. In this study, multiple linear regression analysis techniques were used in the e-views 9 application. The results showed a significant score of 0.4747 > If the significance level was 0.05, there was no relationship between capital intensity and tax aggression. Significant benefits 0.0002 0.05 indicate a relationship between marketing costs and aggressive tax collection. There is no correlation between inventory intensity and other factors, with a significant score of 0.6820 > 0.05. tax aggressiveness